"Development Of Information in Service Fields" - Kholdarov Abdumalik Abdurakhim o‘g‘li (Global Scientific Publishing, 2024)
It is recommended that service providers use good systems to overcome these problems, support practical methods to solve one of the non-unique security problems, and manage their interactions with customers well.
Keywords: Services; organizations; information; security